Traditional Healing Practices in Tharu Community of Lamahi-4, Dang, Nepal - Raut, Bechan; Chaudhary, Ashish; Khanal, Dharma Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: The use of the traditional healing practices is deeply rooted in Nepalese culture and are based on beliefs and historical experiences accumulated from generation to generation. In Nepal, over 60 traditions exist and about 85% of the population depends on traditional medicines for their basic healthcare. The Tharu are the largest indigenous ethnic group in Nepal’s Terai region, practicing traditional medicines in their community since long time. This study mainly focuses on the survey of traditional healing practice including plant used and dhami-jhakri of Thanu community of Dang district Nepal. Method: It was cross sectional descriptive study. The survey was performed to collect the data in Tharu community of Lamahi-4, Dang by using open ended questionnaire and face to face interview. Results: The maximum traditional healers were between age group 61-70 i.e. 37.14% and dominated by male i.e. 85.71%. Majority of traditional healers were engaged in agriculture and 97.145% of traditional healers were illiterate. The diseases were diagnosed by observation and complaint of patient, aksheta herne, traditional mantra, touching body parts etc. Various treatment methods used by traditional healers were aksheta herne, phukphak, body massage, yoga and herbal plants. 76 plant species belonged to 42 families were used by healers for preparing different herbal formulation to cure the different ailments Conclusion: Traditional healing practices was widely used as means of primary healthcare in study area and this area was rich in medicinal plants that have significant role in treatment of different ailments. The widespread use of some medical plants caused the extinction of valuable plant; hence those plants must be preserved for future use.